Komunitas Spons (Porifera) pada Ekosistem Terumbu Karang di Manokwari, Indonesia - Nelly Sayori; Tresia S. Tururaja; Duaitd Kolibongso (Universitas Diponegoro, 2022)
Sponges are one of the most influential benthic organisms in coral reef ecosystems. Many studies on sponge communities have been carried out globally, from the tropics to the sub-tropics. However, in Indonesia, the sponge community has not been sufficiently observed, especially its diversity and interactions with habitats. Manokwari, a developing city north of the Bird's Head Seascape region, Papua has a lack of information on benthic communities and no reports of sponges. This study is to examine the sponge community (diversity and distribution) in coral reef ecosystem. This study found that sponge richness (species and morphology) was categorized as “low”, with only 11 species with 8 morphological forms. The most common species included Niphates erecta, Stylissa carteri, and Pseudoceratina purpurea, while the most common growth forms were massive and encrusting, accounting respectively for 27.3% and 18.2% of the total number of species. The highest diversity was found on the island of Kaki (5 species) with the island of Nusmapi having an uneven distribution of sponges. The results of our study found that there was no relationship between sponge diversity and morphology. This baseline information is essential for management of marine biodiversity hotspots in taking decisions for marine life conservation. Spons merupakan salah satu organisme bentik yang paling berpengaruh dalam ekosistem terumbu karang. Banyak penelitian tentang komunitas spons telah dilakukan secara global, dari daerah tropis hingga sub tropis. Namun di Indonesia, komunitas spons belum cukup diamati, terutama keanekaragaman dan interaksinya dengan habitat. Manokwari, kota berkembang di utara dari wilayah Bentang Laut Kepala Burung (BLKB), Papua memiliki kekurangan informasi tentang komunitas bentik dan tidak ada laporan tentang spons. Studi ini untuk mengkaji komunitas spons (keanekaragaman dan distribusi) pada ekosistem terumbu karang. Penelitian ini menemukan kekayaan spons (spesies dan morfologi) yang dikategorikan “rendah”, dengan hanya 11 spesies dengan 8 bentuk morfologi. Spesies yang paling umum termasuk Niphates erecta, Stylissa carteri, dan Pseudoceratina purpurea, sedangkan bentuk pertumbuhan yang paling umum adalah massif dan encrusting dengan menyumbang masing-masing 27,3% dan18,2% dari total jumlah spesies. Keanekaragaman tertinggi ditemukan di pulau Kaki (5 spesies) dengan pulau Nusmapi memiliki sebaran spons tidak merata. Hasil penelitian kami menemukan tidak ada hubungan antara keanekaragaman spons dengan bentuk morfologi. Informasi dasar ini sangat penting untuk pengelolaan hotspot keanekaragaman hayati dalam perumusan keputusan untuk konservasi biota laut.